Library co-operation - Jefferson, George (London : A Grafton Book- Andre Deutsch, 1966)
It emphasizes the need for cooperation among libraries as well as the tolls of cooperation.
Includes index.
Includes bibliographical references: p. 143-156.
kjo 18/01/2019
Loans
Keywords: Library cooperation